Effects of Aging and Caloric Restriction on Fiber Type Composition, Mitochondrial Morphology and Dynamics in Rat Oxidative and Glycolytic Muscles - Faitg, Julie; Leduc-Gaudet, Jean-Philippe; Reynaud, Olivier; Ferland, Guylaine; Gaudreau, Pierrette; Gouspillou, Gilles (Frontiers in Physiology, 2019)
Aging is associated with a progressive decline in muscle mass and strength, a process known as sarcopenia. Evidence indicates that mitochondrial dysfunction plays a causal role in sarcopenia and suggests that alterations in mitochondrial dynamics/morphology may represent an underlying mechanism. Caloric restriction (CR) is amongst the most efficient non-pharmacological interventions to attenuate sarcopenia in rodents and is thought to exert its beneficial effects by improving mitochondrial function. However, CR effects on mitochondrial morphology and dynamics, especially in aging muscle, remain unknown. To address this issue, we investigated mitochondrial morphology and dynamics in the oxidative soleus (SOL) and glycolytic white gastrocnemius (WG) muscles of adult (9-month-old) ad libitum-fed (AL; A-AL), old (22-month-old) AL-fed (O-AL) and old CR (O-CR) rats. We show that CR attenuates the aging-related decline in the muscle-to-body-weight ratio, a sarcopenic index. CR also prevented the effects of aging on muscle fiber type composition in both muscles. With aging, the SOL displayed fragmented SubSarcolemmal (SS) and InterMyoFibrillar (IMF) mitochondria, an effect attenuated by CR. Aged WG displayed enlarged SS and more complex/branched IMF mitochondria. CR had marginal anti-aging effects on WG mitochondrial morphology. In the SOL, DRP1 (pro-fission protein) content was higher in O-AL vs YA-AL and Mfn2 (pro-fusion) content was higher in O-CR vs A-AL. In the gastrocnemius, Mfn2, Drp1 and Fis1 (pro-fission) contents were higher in O-AL vs A-AL. CR reduced this aging-related increase in Mfn2 and Fis1 content. Overall, these results reveal for the first time that aging differentially impacts mitochondrial morphology and dynamics in different muscle fiber types, by increasing fission/fragmentation in oxidative fibers while enhancing mitochondrial size and branching in glycolytic fibers. Our results also indicate that although CR partially attenuates aging-related changes in mitochondrial dynamics in glycolytic fibers, its anti-aging effect on mitochondrial morphology is restricted to oxidative fibers.